2022
DOI: 10.1002/term.3368
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term passages of human clonal mesenchymal stromal cells can alleviate the disease in the rat model of collagen‐induced arthritis resembling early passages of different heterogeneous cells

Abstract: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease of unknown cause. The interaction of immune system cells and the secretion of inflammatory cytokines with synovial cells leads to severe inflammation in the affected joints. Currently, medications, including non‐steroidal anti‐inflammatory drugs, glucocorticoids, and more recently, disease‐modifying anti‐rheumatic drugs, are used to reduce inflammation. However, long‐term use of these drugs causes adverse effects or resistance in a considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…A classic experimental animal model of human rheumatoid arthritis, complete Freund's adjuvantinduced rheumatoid arthritis is widely used to explore anti-arthritic drugs. The mouse model of arthritis produced by collagen antibodies is one of the other models 26 , pristine-induced arthritis 27 , rat collagen-induced arthritis 28 and Collagen Type II Induced Arthritic 29 . Animals vaccinated with CFA have been reported to have a significant inflammatory response following the inoculation which can lead to substantial joint remodelling and edoema 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A classic experimental animal model of human rheumatoid arthritis, complete Freund's adjuvantinduced rheumatoid arthritis is widely used to explore anti-arthritic drugs. The mouse model of arthritis produced by collagen antibodies is one of the other models 26 , pristine-induced arthritis 27 , rat collagen-induced arthritis 28 and Collagen Type II Induced Arthritic 29 . Animals vaccinated with CFA have been reported to have a significant inflammatory response following the inoculation which can lead to substantial joint remodelling and edoema 30 .…”
Section: Discussionmentioning
confidence: 99%
“…; https://doi.org/10.1101/2024.03. 28.587315 doi: bioRxiv preprint Medication used to control and decrease inflammatory crises includes immunosuppressants, steroids, and nonsteroid anti-inflammatory medicines; however, these drugs are costly and have deleterious effects 8 . Many plant components, including leaves, stems, bark, roots, and so forth, are employed in order to prevent, relieve, or return anomalies to normal 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed a significant decrease in specific IgG levels autoantibodies across all three MSC treatment groups compared to the sham group. This provides strong evidence for the ability of MSCs to reduce serum levels of autoreactive antibodies against CII, specifically CII-specific IgG, and to modulate humoral-specific immune responses against it [ 21 ].…”
Section: Mechanisms Underlying Ra Pathogenesismentioning
confidence: 99%
“…Various preclinical studies have extensively investigated the use of MSCs in tissue repair, yielding encouraging results [ 34 ]. In addition to their capability for tissue regeneration, the immunomodulatory effects of MSCs have been proven in various studies [ 21 , 35 , 36 ]. These properties of MSCs have led to their use in the treatment of autoimmune diseases and graft versus host disease (GvHD) in recent decades with promising results [ 37 ].…”
Section: Stem Cell Therapy For Ramentioning
confidence: 99%
See 1 more Smart Citation